Adsorption technology in water treatment : fundamentals, processes, and modeling / Eckhard Worch. - Worch, Eckhard, 1951- (De Gruyter, 2021)
This title treats the theoretical fundamentals of adsorption technology for water treatment from a practical perspective. It presents all the basics needed for experimental adsorption studies as well as for process modeling and adsorber design. According to the increasing importance of micropollutants in the water cycle, particular attention is paid to their competitive adsorption in the presence of background organic matter.